Accounting frauds – review of advanced technologies to detect and prevent frauds - Y.Segal, Shay (Economics and Business Review, 2016)
In past decades, accounting fraud has adversely affected economies worldwide.Therefore, effective measures and methods ought to be employed in order to efficientlyprevent and detect accounting fraud in a rapidly changing and technologybasedbusiness environment. Data mining methods can assist in prevention and detectionof fraudulent transactions as it enables the use of past cases of fraud to buildmodels that can recognize and spot the risk of fraud and can design new techniques forpreventing fraudulent financial reporting. This article reviews the concept of accountingfraud, and focuses on some of the available data mining tools and methodologies, as well as other commuter-based techniques and tools that are available to order toassist in preventing accounting fraud and detecting if fraudulent acts have been committed.The article asserts the importance of using the available computer-based anddata mining techniques as a prevention mechanism by detecting financial statementfraud, concluding that data mining software propose a good supporting procedurewhich offers an effective solution to the problem of detecting fraudulent transactionsand accounting frauds.